Interfacial Tension of Aqueous and Hydrocarbon Systems in the Presence of Carbon Dioxide at Elevated Pressures and Temperatures - Georgiadis,A (2001)
The interfacial tension of partially miscible phases, containing H2O andhydrocarbons in the presence of CO2 at elevated pressures and temperatures,has been studied within the context of producing cleaner fossil fuelsby simultaneously tackling greenhouse gas emissions. This is a most relevantproperty inuencing the multiphase reservoir ows associated withenhanced oil recovery (EOR), and carbon capture and storage (CCS). Themain core of the thesis focuses on the experimental investigation of thedependence of interfacial tension on pressure and temperature, for variousmixtures of pure substances relevant to oil- eld conditions and uids. Forthis purpose, a high pressure high temperature (HPHT) apparatus, comprisinga view cell, high pressure capillary tubing connections, and appropriateuid delivery syringe pumps, was used over an operating temperaturerange of (298 to 473)K and at pressures up to 60MPa. The apparatusimplemented the pendant drop method, well suited for the accuratedetermination of uid/liquid interfacial tensions at elevated pressures andtemperatures, linked to a computer-aided drop shape analysis (DSA) system.Measurements were made over a wide range of conditions for the twophasesystems (H2O+CO2), (n-decane+CO2), (n-dodecane+CO2), (n-hexadecane+CO2), (H2O+n-decane) and (H2O+[n-decane+CO2]). Thedi erent isotherms recorded for each system demonstrated systematic trendswith increasing pressure, while the decrease of interfacial tension with temperatureobserved at ambient pressures was usually reversed at elevatedpressures. For the (H2O+CO2) system in particular, the pressure dependenceof interfacial tension demonstrated abrupt changes at certain conditions,associated with the onset of the liquid or supercritical states, abovewhich the interfacial tension was less sensitive to changes in both pressureand temperature. This was not the case for the (n-alkane+CO2) systems,where the interfacial tension reduced with increasing pressure, vanishing asthe two phases be